2014
DOI: 10.1055/s-0034-1383065
|View full text |Cite
|
Sign up to set email alerts
|

“Pregnant and Operating”: Evaluation of a Germany-wide Survey Among Female Gynaecologists and Surgeons

Abstract: The current law on the protection of expectant and nursing mothers largely rules out surgical activities during pregnancy for female doctors who perform surgical roles in hospitals. The proportion of female junior staff in gynaecology amounts to 80?%, and, for many of these women, surgical further training is not possible following official notification of an existing pregnancy. In a Germany-wide survey of female gynaecologists and surgeons using a questionnaire, it was determined to what extent female doctors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 13 publications
2
34
0
10
Order By: Relevance
“…Most respondents wished for a change in the German law on the protection of expectant and nursing mothers to continue working in surgery during pregnancy [18]. We need to identify such notable barriers to achieving desired career intentions in this highly motivated workforce of female surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Most respondents wished for a change in the German law on the protection of expectant and nursing mothers to continue working in surgery during pregnancy [18]. We need to identify such notable barriers to achieving desired career intentions in this highly motivated workforce of female surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Most of listed risk factors have been analysed in various studies in order to examine whether there is any association between performing surgeries and unfavourable pregnancy outcomes such as miscarriage, intrauterine growth restriction (IUGR) or preterm delivery. A questionnaire conducted in Germany did not reveal any increase in the risk of complications among pregnant surgeons in comparison to the general population [2]. Another study proved a correlation between preterm delivery and long working hours, shift work, lifting, standing and heavy physical workload, all of which are included in surgeon's activities [3].…”
Section: Introductionmentioning
confidence: 97%
“…It is not clearly restricted, at which stage of gestation women are advised to stop operating. Moreover, it is shown that there is a predilection among consultants to cease operating significantly later in comparison to assistant doctors [2]. Also, more experienced surgeons holding higher positions show a tendency to inform their supervisors about their pregnancy later than their younger colleagues [2].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations